Deteksi Megalocytivirus pada Ikan Bawal Bintang (Trachinotus blochii) dengan Metode Real-Time PCR - Olvyra Dwisafitri, Karin; Elviantari, Adelia (BIOMARAS : Journal of Life Science and Technology, 2025)
Pomfret (Trachinotus blochii) is a type of fish that has great potential to be cultivated and has high economic value, both in local and international markets. However, one of the challenges in its cultivation is infection by pathogenic microorganisms, including viruses. One of the viruses that can infect pomfret fish is Megalocytivirus. Fish infected with Megalocytivirus generally show clinical symptoms in the form of behavioral changes, such as decreased appetite, weak swimming and less activity. Rapid and accurate detection methods are needed to effectively identify the presence of Megalocytivirus. This research aims to detect Megalocytivirus in pomfret fish cultivated at BPBL, Lombok using Real-Time PCR. This research method includes taking, extracting DNA samples and amplifying DNA. The results showed that pomfret fish were positive for Megalocytivirus attack, characterized by an accumulation of fluorescent signals that crossed the threshold line with a cycle threshold (Ct) or quantification cycle value of <35.